Can more than one incremental cycling test be performed within one day? - Scharhag-Rosenberger, F.; Carlsohn, A.; Lundby, C.; Schüler, S.; Mayer, F.; Scharhag, J. (European Journal of Sport Science, 2014)
Changes in performance parameters over four consecutive maximal incremental cycling tests were investigated to determine how many tests can be performed within one single day without negatively affecting performance. Sixteen male and female subjects (eight trained (T): 25 ± 3 yr, BMI 22.6 ± 2.5 kg·m-2, maximal power output (Pmax) 4.6 ± 0.5 W·kg-1; eight untrained (UT): 27 ± 3 yr, BMI 22.3 ± 1.2 kg·m-2, Pmax 2.9 ± 0.3 W·kg-1) performed four successive maximal incremental cycling tests separated by 1.5 h of passive rest. Individual energy requirements were covered by standardised meals between trials. Maximal oxygen uptake (VO2max) remained unchanged over the four tests in both groups (P = 0.20 and P = 0.33, respectively). Pmax did not change in the T group (P = 0.32), but decreased from the third test in the UT group (P < 0.01). Heart rate responses to submaximal exercise were elevated from the third test in the T group and from the second test in the UT group (P < 0.05). The increase in blood lactate shifted rightward over the four tests in both groups (P < 0.001 and P < 0.01, respectively). Exercise-induced net increases in epinephrine and norepinephrine were not different between the tests in either group (P >/= 0.15). If VO2max is the main parameter of interest, trained and untrained individuals can perform at least four maximal incremental cycling tests per day. However, because other parameters changed after the first and second test, respectively, no more than one test per day should be performed if parameters other than VO2max are the prime focus.